Shakedown analysis of pile foundations under cyclic lateral loadings - Tang, Xiaojun (2021)
Pile foundations for many infrastructures, such as bridges, oil rigs, electricity towers, wind, and wave turbines, sustain cyclic lateral loads from wind or wave actions. The long-term response of pile foundations under cyclic lateral loading conditions is one key factor to consider in the design, which is commonly explored by cyclic pile load tests or step-by-step numerical procedures with empirical degradation factors. Shakedown analysis provides an alternative and efficient means of predicting limiting loads of the pile foundations against excessive accumulated permanent deformation under cyclic lateral loads.